Improved admixture vaccine of fentanyl and heroin hapten immunoconjugates: Antinociceptive evaluation of fentanyl-contaminated heroin - Hwang, Candy S.; Smith, Lauren C.; Natori, Yoshihiro; Ellis, Beverly; Zhou, Bin; Janda, Kim D. (ACS Omega, 2018)
Fentanyl and its derivatives have become pervasive contaminants in the U.S. heroin supply. Previously, we reported a proof-of-concept vaccine designed to combat against heroin contaminated with fentanyl. Herein, we optimized the admixture vaccine and found that it surpassed the individual vaccines in every antinociceptive test, including a 10% fentanyl to heroin formulation. It is anticipated that other co-occurring drug abuse disorders may also be examined with admixture vaccines. © 2018 American Chemical Society.
31 citations (Crossref) [2023-10-31]
Keywords: dept.che; peer-reviewed

A chemically contiguous hapten approach for a heroin-fentanyl vaccine. - Natori, Yoshihiro; Hwang, Candy S; Lin, Lucy; Smith, Lauren C; Zhou, Bin; Janda, Kim D (Beilstein journal of organic chemistry, 2019)
Background: Increased death due to the opioid epidemic in the United States has necessitated the development of new strategies to treat addiction. Monoclonal antibodies and antidrug vaccines provide a tool that both aids addiction management and reduces the potential for overdose. Dual drug vaccines formulated by successive conjugation or by mixture have certain drawbacks. The current study examines an approach for combatting the dangers of fentanyl-laced heroin, by using a hapten with one epitope that has domains for both fentanyl and heroin. Results: We evaluated a series of nine vaccines developed from chemically contiguous haptens composed of both heroin- and fentanyl-like domains. Analysis of the results obtained by SPR and ELISA revealed trends in antibody affinity and titers for heroin and fentanyl based on epitope size and linker location. In antinociception studies, the best performing vaccines offered comparable protection against heroin as our benchmark heroin vaccine, but exhibited attenuated protection against fentanyl compared to our fentanyl vaccine. Conclusion: After thorough investigation of this strategy, we have identified key considerations for the development of a chemically contiguous heroin-fentanyl vaccine. Importantly, this is the first report of such a strategy in the opioid-drug-vaccine field.
21 citations (Crossref) [2023-10-31] Place: Germany Natori, Yoshihiro. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology; The Scripps Research Institute, 10550 N Torrey Pines Rd, La Jolla, CA, 92037, USA. Natori, Yoshihiro. Faculty of Pharmaceutical Sciences, Tohoku Medical and Pharmaceutical University, Komatsushima 4-4-1, Aoba-ku, Sendai, 981-8558, Japan. Hwang, Candy S. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology; The Scripps Research Institute, 10550 N Torrey Pines Rd, La Jolla, CA, 92037, USA. Hwang, Candy S. Department of Chemistry, Southern Connecticut State University, 501 Crescent St, New Haven, CT, 06515, USA. Lin, Lucy. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology; The Scripps Research Institute, 10550 N Torrey Pines Rd, La Jolla, CA, 92037, USA. Smith, Lauren C. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology; The Scripps Research Institute, 10550 N Torrey Pines Rd, La Jolla, CA, 92037, USA. Zhou, Bin. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology; The Scripps Research Institute, 10550 N Torrey Pines Rd, La Jolla, CA, 92037, USA. Janda, Kim D. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology; The Scripps Research Institute, 10550 N Torrey Pines Rd, La Jolla, CA, 92037, USA.
Keywords: Antinociception; Fentanyl; Hapten; Heroin; Vaccine; dept.che; peer-reviewed

Sex Differences in Response to a 12-Week Resistance Training Exercise Intervention After Cardiac Surgery: A Proof-of-Concept Intervention Trial - Safdar, Basmah; Jarman, Angela; Madsen, Tracy; DeLamielleure, Lauren; Zhou, Bin; Axtell, Robert; Geirsson, Arnar; Mangi, Abeel (Clinical Therapeutics, 2025)
Keywords: Cardiac rehabilitation (CR); Cardiac surgery; Cardiovascular disease (CVD); Intervention (counseling); Medicine; Nursing; Physical therapy; Randomized controlled trial; Resistance strength training; Resistance training; Safety and feasibility; Sex differences; Surgery; dept.hms; peer-reviewed

Monoclonal Antibodies for Combating Synthetic Opioid Intoxication. - Smith, Lauren C; Bremer, Paul T; Hwang, Candy S; Zhou, Bin; Ellis, Beverly; Hixon, Mark S; Janda, Kim D (Journal of the American Chemical Society, 2019)
Opioid abuse in the United States has been declared a national crisis and is exacerbated by an inexpensive, readily available, and illicit supply of synthetic opioids. Specifically, fentanyl and related analogues such as carfentanil pose a significant danger to opioid users due to their high potency and rapid acting depression of respiration. In recent years these synthetic opioids have become the number one cause of drug-related deaths. In our research efforts to combat the public health threat posed by synthetic opioids, we have developed monoclonal antibodies (mAbs) against the fentanyl class of drugs. The mAbs were generated in hybridomas derived from mice vaccinated with a fentanyl conjugate vaccine. Guided by a surface plasmon resonance (SPR) binding assay, we selected six hybridomas that produced mAbs with 10-11 M binding affinity for fentanyl, yet broad cross-reactivity with related fentanyl analogues. In mouse antinociception models, our lead mAb (6A4) could blunt the effects of both fentanyl and carfentanil in a dose-responsive manner. Additionally, mice pretreated with 6A4 displayed enhanced survival when subjected to fentanyl above LD50 doses. Pharmacokinetic analysis revealed that the antibody sequesters large amounts of these drugs in the blood, thus reducing drug biodistribution to the brain and other tissue. Lastly, the 6A4 mAb could effectively reverse fentanyl/carfentanil-induced antinociception comparable to the opioid antagonist naloxone, the standard of care drug for treating opioid overdose. While naloxone is known for its short half-life, we found the half-life of 6A4 to be approximately 6 days in mice, thus monoclonal antibodies could theoretically be useful in preventing renarcotization events in which opioid intoxication recurs following quick metabolism of naloxone. Our results as a whole demonstrate that monoclonal antibodies could be a desirable treatment modality for synthetic opioid overdose and possibly opioid use disorder.
39 citations (Crossref) [2023-10-31] Place: United States Smith, Lauren C. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology, The Scripps Research Institute, 10550 N Torrey Pines Road, La Jolla, California 92037, United States. Bremer, Paul T. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology, The Scripps Research Institute, 10550 N Torrey Pines Road, La Jolla, California 92037, United States. Bremer, Paul T. Cessation Therapeutics LLC, 3031 Tisch Way Ste 505, San Jose, California 95128, United States. Hwang, Candy S. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology, The Scripps Research Institute, 10550 N Torrey Pines Road, La Jolla, California 92037, United States. Hwang, Candy S. Department of Chemistry, Southern Connecticut State University, New Haven, Connecticut 06515, United States. Zhou, Bin. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology, The Scripps Research Institute, 10550 N Torrey Pines Road, La Jolla, California 92037, United States. Ellis, Beverly. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology, The Scripps Research Institute, 10550 N Torrey Pines Road, La Jolla, California 92037, United States. Hixon, Mark S. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology, The Scripps Research Institute, 10550 N Torrey Pines Road, La Jolla, California 92037, United States. Hixon, Mark S. Mark S. Hixon Consulting LLC, 11273 Spitfire Road, San Diego, California 92126, United States. Janda, Kim D. Departments of Chemistry, Immunology and Microbial Science, Skaggs Institute for Chemical Biology, The Scripps Research Institute, 10550 N Torrey Pines Road, La Jolla, California 92037, United States.
Keywords: *Analgesics; Opioid/ai [Antagonists & Inhibitors]; *Antibodies; Monoclonal/pd [Pharmacology]; *Narcotic Antagonists/pd [Pharmacology]; *Nociceptive Pain/dt [Drug Therapy]; *Opioid-Related Disorders/dt [Drug Therapy]; Analgesics; Opioid; Analgesics; Opioid/ad [Administration & Dosage]; Anesthetics; Animals; Antibodies; Monoclonal; Antibodies; Monoclonal/ad [Administration & Dosage]; Antibodies; Monoclonal/ch [Chemistry]; Article; Binding affinities; Binding energy; Biodistributions; Conjugate vaccine; Cross reactivity; Health risks; IC50; Mammals; Mice; Monoclonal antibodies; Monoclonal antibodies (mAbs); Narcotic Antagonists; Narcotic Antagonists/ad [Administration & Dosage]; Narcotic Antagonists/ch [Chemistry]; Nociceptive Pain; Opioid-Related Disorders; Pharmacokinetic analysis; Standard of cares; Surface Plasmon Resonance; Surface plasmon resonance; Treatment modality; animal; animal experiment; animal model; antibody production; antinociception; binding affinity; carfentanil; chemistry; controlled study; cross reaction; dept.che; drug distribution; drug half life; drug intoxication; drug metabolism; drug overdose; drug structure; fentanyl; hybridoma; immunization; in vivo study; liquid chromatography-mass spectrometry; male; monoclonal antibody; monoclonal antibody 6A4; mouse; naloxone; narcotic analgesic agent; narcotic antagonist; nociceptive pain; nonhuman; opiate; opiate addiction; opioid intoxication; peer-reviewed; purification; surface plasmon resonance; unclassified drug

Vaccine blunts fentanyl potency in male rhesus monkeys - Tenney, Rebekah D.; Blake, Steven; Bremer, Paul T.; Zhou, Bin; Hwang, Candy S.; Poklis, Justin L.; Janda, Kim D.; Banks, Matthew L. (Neuropharmacology, 2019)
One proposed factor contributing to the increased frequency of opioid overdose deaths is the emergence of novel synthetic opioids, including illicit fentanyl and fentanyl analogues. A treatment strategy currently under development to address the ongoing opioid crisis is immunopharmacotherapies or opioid-targeted vaccines. The present study determined the effectiveness and selectivity of a fentanyl-tetanus toxoid conjugate vaccine to alter the behavioral effects of fentanyl and a structurally dissimilar mu-opioid agonist oxycodone in male rhesus monkeys (n = 3-4). Fentanyl and oxycodone produced dose-dependent suppression of behavior in an assay of schedule-controlled responding and antinociception in an assay of thermal nociception (50 degrees C). Acute naltrexone (0.032 mg/kg) produced an approximate 10-fold potency shift for fentanyl to decrease operant responding. The fentanyl vaccine was administered at weeks 0, 2, 4, 9, 19, and 44 and fentanyl or oxycodone potencies in both behavioral assays were redetermined over the course of 49 weeks. The vaccine significantly and selectively shifted fentanyl potency at least 10-fold in both assays at several time points over the entire experimental period. Mid-point titer levels correlated with fentanyl antinociceptive potency shifts. Antibody affinity for fentanyl as measured by a competitive binding assay improved over time to approximately 3-4 nM. The fentanyl vaccine also increased fentanyl plasma levels approximately 6-fold consistent with the hypothesis that the vaccine sequesters fentanyl in the blood. Overall, these results support the continued development and evaluation of this fentanyl vaccine in humans to address the ongoing opioid crisis.
37 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000488998500026 tex.article-number: [object Object] tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Antinociception; Fentanyl; Naltrexone; Oxycodone; Rhesus monkeys; Vaccine; dept.che; peer-reviewed

Conjugate vaccine produces long-lasting attenuation of fentanyl vs. food choice and blocks expression of opioid withdrawal-induced increases in fentanyl choice in rats. - Townsend, E Andrew; Blake, Steven; Faunce, Kaycee E; Hwang, Candy S; Natori, Yoshihiro; Zhou, Bin; Bremer, Paul T; Janda, Kim D; Banks, Matthew L (Neuropsychopharmacology : official publication of the American College of Neuropsychopharmacology, 2019)
The current opioid crisis remains a significant public health issue and there is a critical need for biomedical research to develop effective and easily deployable candidate treatments. One emerging treatment strategy for opioid use disorder includes immunopharmacotherapies or opioid-targeted vaccines. The present study determined the effectiveness of a fentanyl-tetanus toxoid conjugate vaccine to alter fentanyl self-administration using a fentanyl-vs.-food choice procedure in male and female rats under three experimental conditions. For comparison, continuous 7-day naltrexone (0.01-0.1 mg/kg/h) and 7-day clonidine (3.2-10 mug/kg/h) treatment effects were also determined on fentanyl-vs.-food choice. Male and female rats responded for concurrently available 18% diluted Ensure R (liquid food) and fentanyl (0-10 mug/kg/infusion) infusions during daily sessions. Under baseline and saline treatment conditions, fentanyl maintained a dose-dependent increase in fentanyl-vs.-food choice. First, fentanyl vaccine administration significantly blunted fentanyl reinforcement and increased food reinforcement for 15 weeks in non-opioid dependent rats. Second, surmountability experiments by increasing the unit fentanyl dose available during the self-administration session 10-fold empirically determined that the fentanyl vaccine produced an approximate 22-fold potency shift in fentanyl-vs.-food choice that was as effective as the clinically approved treatment naltrexone. Clonidine treatment significantly increased fentanyl-vs.-food choice. Lastly, fentanyl vaccine administration prevented the expression of withdrawal-associated increases in fentanyl-vs.-food choice following introduction of extended 12 h fentanyl access sessions. Overall, these results support the potential and further consideration of immunopharmacotherapies as candidate treatments to address the current opioid crisis.
52 citations (Crossref) [2023-10-31] Place: England Townsend, E Andrew. Department of Pharmacology and Toxicology, Virginia Commonwealth University School of Medicine, Richmond, VA, 23298, USA. Blake, Steven. Departments of Chemistry and Immunology and Microbial Science, Skaggs Institute for Chemical Biology, Worm Institute for Research and Medicine, The Scripps Research Institute, La Jolla, CA, 92037, USA. Faunce, Kaycee E. Department of Pharmacology and Toxicology, Virginia Commonwealth University School of Medicine, Richmond, VA, 23298, USA. Hwang, Candy S. Departments of Chemistry and Immunology and Microbial Science, Skaggs Institute for Chemical Biology, Worm Institute for Research and Medicine, The Scripps Research Institute, La Jolla, CA, 92037, USA. Hwang, Candy S. Department of Chemistry, Southern Connecticut State University, 501 Crescent St, New Haven, CT, 06515, USA. Natori, Yoshihiro. Departments of Chemistry and Immunology and Microbial Science, Skaggs Institute for Chemical Biology, Worm Institute for Research and Medicine, The Scripps Research Institute, La Jolla, CA, 92037, USA. Natori, Yoshihiro. Faculty of Pharmaceutical Sciences, Tohoku Medical and Pharmaceutical University, Komatsushima 4-4-1, Aoba-ku, Sendai, 981-8558, Japan. Zhou, Bin. Departments of Chemistry and Immunology and Microbial Science, Skaggs Institute for Chemical Biology, Worm Institute for Research and Medicine, The Scripps Research Institute, La Jolla, CA, 92037, USA. Bremer, Paul T. Departments of Chemistry and Immunology and Microbial Science, Skaggs Institute for Chemical Biology, Worm Institute for Research and Medicine, The Scripps Research Institute, La Jolla, CA, 92037, USA. Janda, Kim D. Departments of Chemistry and Immunology and Microbial Science, Skaggs Institute for Chemical Biology, Worm Institute for Research and Medicine, The Scripps Research Institute, La Jolla, CA, 92037, USA. kdjanda@scripps.edu. Banks, Matthew L. Department of Pharmacology and Toxicology, Virginia Commonwealth University School of Medicine, Richmond, VA, 23298, USA. mbanks7@vcu.edu. Comment in (CIN)
Keywords: *Analgesics; Opioid/ad [Administration & Dosage]; *Analgesics; Opioid/im [Immunology]; *Behavior; Animal/de [Drug Effects]; *Choice Behavior/de [Drug Effects]; *Drug-Seeking Behavior/de [Drug Effects]; *Fentanyl/ad [Administration & Dosage]; *Fentanyl/im [Immunology]; *Vaccines; Conjugate/pd [Pharmacology]; Adrenergic alpha-2 Receptor Agonists; Adrenergic alpha-2 Receptor Agonists/pd [Pharmacology]; Analgesics; Opioid; Animals; Article; Behavior; Animal; Choice Behavior; Clonidine; Clonidine/pd [Pharmacology]; CpG oligodeoxynucleotide; Drug-Seeking Behavior; Feeding Behavior; Feeding Behavior/de [Drug Effects]; Female; Fentanyl; Food; Male; Naltrexone; Naltrexone/pd [Pharmacology]; Narcotic Antagonists; Narcotic Antagonists/pd [Pharmacology]; Opioid-Related Disorders; Rats; Reinforcement; Psychology; Self Administration; Substance Withdrawal Syndrome; Substance Withdrawal Syndrome/pp [Physiopathology]; Tetanus Toxoid; Vaccines; Conjugate; alpha 2 adrenergic receptor stimulating agent; aluminum hydroxide; animal; animal behavior; animal experiment; animal model; antinociception; clinical effectiveness; clinical evaluation; clonidine; comparative study; controlled study; decision making; dept.che; drug conjugation; drug effect; drug infusion; drug seeking behavior; drug self administration; ensure; feeding behavior; female; fentanyl; fentanyl tetanus toxoid conjugate vaccine; food; food intake; immunology; male; naltrexone; narcotic analgesic agent; narcotic antagonist; nonhuman; opiate addiction; opioid use disorder; pathophysiology; peer-reviewed; priority journal; protein expression; rat; reinforcement; sodium chloride; tetanus toxoid; time to treatment; unclassified drug; vaccination; vaccine; withdrawal syndrome